(untitled) (Journal of Food and Dietetics Research, 2021)
Objectives: Bread, holds its place and grace from ancient days as it is the food for any person on any day, at any time, and anywhere. Bread is the most preferred soft diet because of the easy availability and convenience to carry. Bread is usually prepared by refined wheat flour and hence high in calories making it a less prioritized food for persons with metabolic disorders. Hence, this study is framed with the objective of enriching the nutritional quality of bread by incorporation of Ocimum basilicum seeds flour. Material and Methods: The Ocimum basilicum seeds flour in a proportion of 5%, 10%, 15% and 20% of the wheat flour was substituted in the variations BV1, BV2, BV3, BV4 and the bread was prepared by following standardised baking procedures. All the variations of Ocimum basilicum seed flour incorporated breads were subjected to proximate, texture and organoleptic analysis. Results: The results depicted that the proximate composition viz. moisture, energy, protein, fat, ash and fibre, of the Ocimum basilicum seed flour incorporated bread showed significant difference (p < 0.05) in all the variations, on comparison with control. The 20% O. basilicum seed flour incorporated variation BV4 holds maximum nutrients. The texture profile analysis has shown a significant difference in all the parameters on comparison with the control. The overall acceptability was high for variation BV3, which has 15% of O. basilicum seeds flour incorporation, on organoleptic evaluation. Conclusion: It can be concluded that Ocimum basilicum seed flour can be effectively used in the preparation of bakery products like bread as a means of value addition.